A strategy to achieve enhanced electromagnetic interference shielding at low concentration with a new generation of conductive carbon black in a chlorinated polyethylene elastomeric matrix. Issue 35 (19th August 2016) - Mondal, Subhadip; Ganguly, Sayan; Rahaman, Mostafizur; Aldalbahi, Ali; Chaki, Tapan K.; Khastgir, Dipak; Das, Narayan Ch.
Abstract : A schematic diagram of shielding and conducting phenomena of polymer composites. Abstract : The fabrication of scalable and affordable conductive Ketjen carbon black (K-CB)–elastomer composites for adjustable electromagnetic interference (EMI) shielding remains a difficult challenge. Herein, chlorinated polyethylene (CPE)–K-CB composites have been developed by single step solution mixing to achieve high EMI shielding performance associated with absorption dominance potency by conductive dissipation as well as the reflection of electromagnetic waves. The dispersion of K-CB inside the CPE matrix has been corroborated by electron micrographs and atomic force microscopy (AFM). The K-CB filler and CPE polymer interaction has been investigated through the bound rubber content (Bdr) and the dynamic mechanical properties. The relatively low loading of K-CB with respect to other conventional carbon fillers contributes to a promising low percolation threshold (9.6 wt% K-CB) and a reasonably high EMI shielding effectiveness (EMI SE) value of 38.4 dB (at 30 wt% loading) in the X-band region (8.2 to 12.4 GHz). Classical percolation theory reveals that the electrical conduction behavior through the composite system is quasi-two dimensional in nature. Our belief lies in the promotion of scalable production of flexible and cost-effective K-CB–CPE composites of superior EMI SE to avoid electromagnetic radiation pollution.